2017
DOI: 10.3390/ijms18050981
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Vitamin D Interfere with the Adipogenic Fate of Adipose-Derived Stem Cells

Abstract: Adipose-derived stem cells (ADSCs) represent one of the cellular populations resident in adipose tissue. They can be recruited under certain stimuli and committed to become preadipocytes, and then mature adipocytes. Controlling stem cell differentiation towards the adipogenic phenotype could have a great impact on future drug development aimed at counteracting fat depots. Stem cell commitment can be influenced by different molecules, such as melatonin, which we have previously shown to be an osteogenic inducer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 36 publications
(46 reference statements)
1
69
2
Order By: Relevance
“…Actually, plants and herbs, as active medicinal, are applied to stimulate stem cell proliferation, regeneration and rehabilitation in damaged tissues, being nowadays still employed in the attempt to counteract different groups of diseases [38]. Moreover, different natural compounds, as bioactive molecules are largely used in vitro to condition specific culturing media in the attempt to activate stem cell regenerative potential [39]- [42]. On the other hand, they have been also largely exploited in cancer treatment, for their capability to inhibit cell proliferation and neoplastic progression [43]- [46].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, plants and herbs, as active medicinal, are applied to stimulate stem cell proliferation, regeneration and rehabilitation in damaged tissues, being nowadays still employed in the attempt to counteract different groups of diseases [38]. Moreover, different natural compounds, as bioactive molecules are largely used in vitro to condition specific culturing media in the attempt to activate stem cell regenerative potential [39]- [42]. On the other hand, they have been also largely exploited in cancer treatment, for their capability to inhibit cell proliferation and neoplastic progression [43]- [46].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of thyroid hormone on lipid metabolism is complex and poorly understood. Lipid metabolism is regulated by different enzymes, which are regulated by different specific gene and hormones [20,21] and lack of thyroid hormone causes elevation in total cholesterol and LDLc by changes in the synthesis, metabolism, and mobilisation of lipids [22].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is important in a wide range of physiological processes, and its deficit has been related to different chronic diseases and metabolic conditions, including obesity. Nonetheless, encompassing literature studies indicated only a faint association between gene variants acting in vitamin D metabolism and the obese phenotype [33], while the environment seems to play a major role [34][35][36]. The overall estimate of heritability of 25-hydroxyvitamin D serum concentrations attributable to the six susceptibility loci harboring genome-wide significant SNPs (recently identified in a large GWAS) is 7.5%, with statistically significant loci explaining 38% of this total [37].…”
Section: Discussionmentioning
confidence: 99%